Genealogy : a practical guide for librarians - Pennavaria, Katherine, 1959- (Practical guides for librarians ;, 2015)
Genealogy: A Practical Guide for Librarians covers the big picture of genealogy and evidence-based research, plus the variety and availability of many record types, but also provides practical advice for both researchers and librarians.